Application of Hypnotherapy Techniques to Overcome Ailurophobia - Hidayat, Dea; Gutji, Nelyahardi; Wahyuni, Hera; Yusra, Affan (Journal of Research and Measurement in Psychology: JPPP, 2022)
This study is based on a survey conducted in the environment of researchers who found the presence of phobias or excessive fear of an object, in this case, researchers found cases of one type of phobia, namely Ailurophobia where sufferers are afraid of excessive cat animals. This research aims to analyze the application of hypnotherapy techniques to overcome ailurophobia. This type of research is Action Research (PTL). The study was conducted in (3) three actions, the first action was carried out in 1 (one) week with a frequency of 1 (one) meeting, the second action was carried out based on reflection on the first action, the second action is carried out on the basis of reflection on the first action, and the third action is carried out on the basis of reflection on the second action. Subsequently, the results of the study were reported